A Supramolecular Artificial Light‐Harvesting System with an Ultrahigh Antenna Effect. Issue 30 (6th June 2017) - Li, Jing‐Jing; Chen, Yong; Yu, Jie; Cheng, Ni; Liu, Yu
Abstract : An efficient artificial light‐harvesting system is fabricated from a cyclic polysaccharide, sulfato‐β‐cyclodextrin (SCD); an aggregation‐induced emission molecule, an oligo(phenylenevinylene) derivative (OPV‐I); and a fluorescent dye, nile red (NiR), via noncovalent interactions in an aqueous solution. In this system, the OPV‐I/SCD supramolecular assembly acts as a donor, and NiR that is loaded into the OPV‐I/SCD assembly acts as an acceptor. Significantly, an efficient energy‐transfer process occurs between the OPV‐I/SCD assembly and the loaded NiR, leading to an extremely high antenna effect. Abstract : An efficient artificial light‐harvesting system is fabricated based on a supramolecular strategy in aqueous solution. In this system, the supramolecular assembly acts as a donor, and nile red that is loaded into the assembly acts as acceptor. Significantly, an efficient energy‐transfer process occurs between the assembly and the loaded nile red, leading to an extremely high antenna effect.